Kinobead/LC-MS phosphokinome profiling enables rapid analyses of kinase-dependent cell signaling networks - Golkowski, Martin (J Proteome Res, 2020)
Kinase-catalyzed protein phosphorylation is fundamental to eukaryotic signal transduction, regulating most cellular processes. Kinases are frequently dysregulated in cancer, inflammation and degenerative diseases, and because they can be inhibited with small molecules, they became important drug targets. Accordingly, analytical approaches that determine kinase activation states are critically important to understand kinase-dependent signal transduction, and to identify novel drug targets and predictive biomarkers. Multiplexed inhibitor beads (MIBs or kinobeads) efficiently enrich kinases from cell lysates for LC-MS analysis. When combined with phosphopeptide enrichment, kinobead/LC-MS can also quantify the phosphorylation state of kinases, which determines their activation state. However, an efficient kinobead/LC-MS kinase phospho-profiling protocol that allows routine analyses of cell lines and tissues has not yet been developed. Here, we present a facile workflow that quantifies the global phosphorylation state of kinases with unprecedented sensitivity. We also found that our kinobead/LC-MS protocol can measure changes in kinase complex composition and show how these changes can indicate kinase activity. We demonstrate the utility of our approach in specifying kinase signaling pathways that control the acute steroidogenic response in Leydig cells; this analysis establishes the first comprehensive framework for the post-translational control of steroid biosynthesis.